Pengaruh Interpersonal Trust Terhadap Self-Disclosure Narapidana Pada Petugas Pemasyarakatan di Lembaga Pemasyarakatan Kelas I Tangerang - Widiasmita, Ni Nyoman Fitria; Muhammad , Ali (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
The high recidivism rate/the repetition of criminal acts by prisoners is the impact of the failure to properly classify development program for prisoners. This is because the results of societal research are inaccurate due to the lack of interpersonal trust between prisoners and officer resulting in low of self-disclosure of prisoners to correctional officers. The aim of this research is to determine whether there is an influence between interpersonal trust and self-disclosure of prisoners among correctional officers at the Lembaga Pemasyarakatan I Tangerang. This research is quantitative research using a simple linear regression analysis method. This research was conducted at the Lembaga Pemasyarakatan Kelas I Tangerang. The research samples consisted of 186 male prisoners using purposive sampling technique, where the researcher determines characteristics from the populations adjusted to the purpose of the research. The criteria for respondents were prisoners whose age in the range of 18-59 years. The research data was collected using the Interpersonal Trust Scale by Rotenberg (2010) and Revise Self-Disclosure Scale (RSDS) by Wheeless and Grotz (1978). The research has R value of 0.607 and R Square value of 0.369, significance p 0.000 (